Contemporary Challenges in Endocarditis - Firstenberg, Michael S. (IntechOpen, 2016)
Endocarditis remains an elusive challenge for clinicians to master. As the population ages and their comorbidities increase, the risk of infecting cardiac structures - both native and, the ever-increasing use of, prosthetic support technology - also increases. In addition, the global epidemic of intravenous substance abuse has also resulted in a substantial increase in the number of infected patients. Fortunately, advances in the diagnostic testing, imaging, and recognition of the importance of a multidisciplinary management team have also contributed to advances in the care of these critically ill patients. Nevertheless, optimal therapies need to be individualized and considered in the ever-increasing body of scientific literature on this complex and difficult problem.